Complementary Impact of Carotid Intima–Media Thickness With Plaque in Associations With Noncardiac Arterial Vascular Events. (February 2020) - Kolkenbeck-Ruh, Andrea; Woodiwiss, Angela J.; Monareng, Talib; Sadiq, Eitzaz; Mabena, Philanathi; Robinson, Chanel; Motau, Tshegofatso H.; Stevens, Belinda; Manyatsi, Nomvuyo; Tiedt, Scott; Dembskey, Reinhard; Abdool-Carrim, Talib; et al.
The ability of carotid intima–media thickness (IMT) to predict risk beyond plaque is controversial. In 952 participants (critical limb ischemia [CLI] or stroke, n = 473; community, n = 479), we assessed whether relationships with events for IMT complement the impact of plaque in young patients depending on the extent of thrombotic versus atherosclerotic disease. The extent of atherosclerotic versus thrombotic occlusion was determined in 54 patients with CLI requiring amputations. Thrombotic occlusion in CLI was associated with younger age ( P < .0001) and less plaque ( P = .02). Independent relations between plaque and CLI were noted in older (>50 years; P < .005 to <.0001) but not younger ( P > .38) participants, while independent relations between plaque and stroke ( P < .005 to <.0001) and between IMT and CLI ( P < .0001) were noted in younger participants. Although in performance (area under the receiver operating curve) for event detection, IMT thresholds failed to add to plaque alone in older patients (0.680 ± 0.020 vs 0.664 ± 0.017, P = .27), IMT improved performance for combined stroke and CLI detection when added to plaque in younger patients (0.719 ± 0.023 vs 0.631 ± 0.026, P < .0001). Because in younger participants the high prevalence of thrombotic occlusion in CLI is associated with less plaque, IMT adds information in associations with arterial vascular events.